Large cell neuroendocrine carcinoma of the cervix: a case report - Li, Chunmei; Wu, Maoyuan; Zhang, Wenwen; Jiang, Xiaoling; Zhang, Lixia; Wang, Gangcheng; He, Lianli (Frontiers in Oncology, 2024)
Large Cell Neuroendocrine Carcinoma (LCNEC) of the cervix is an extremely rare but highly aggressive type of cervical cancer and it requires multimodal therapy to improve their quality of life. At present, there are no established, standardized treatment protocols for managing large cell neuroendocrine carcinoma of the cervix. In this report, we present a case of a patient with cervical LCNEC, Who was a 39-year-old woman who presented with irregular vaginal bleeding accompanied by lower abdominal distension for over a month. Examination revealed a cauliflower-like cervical mass approximately 4cm in diameter, with the normal cervical architecture distorted and partially fused to the vaginal wall. Following further investigations, the stage assigned was IVB, and who was started on neoadjuvant chemotherapy with the TC (paclitaxel + carboplatin) regimenand .but during neoadjuvant chemotherapy, The patient developed a vaginal urinary leakage. Then, The patient underwent a comprehensive treatment regimen that included pelvic exenteration, urinary system reconstruction, pelvic floor reconstruction, and chemotherapy. Given the patient's positive immunohistochemistry for EGFR, the treatment was combined with the anti-angiogenic drug, bevacizumab. The patient achieved complete remission following the comprehensive treatment. Through this case to explore individualized treatment for cervical LCNEC.